2005
DOI: 10.1038/sj.thj.6200573
|View full text |Cite
|
Sign up to set email alerts
|

Plasma nitric oxide levels used as an indicator of doxorubicin-induced cardiotoxicity in rats

Abstract: Our results revealed a correlation between plasmatic NO levels, systolic function and histopathological myocardial damage. Therefore, it is plausible to postulate that plasmatic NO levels could be used as a biomarker for myocardial damage in doxorubicin-treated SHR, and may be a potential tool for noninvasive evaluation of doxorubicin-induced toxicity in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Further, arginine represents a by-product of nitric oxide formation. A previous study showed that nitric oxide levels were decreased in DOX-induced congestive heart failure suggesting the possible role of plasma nitric oxide levels in DOX-induced cardiotoxicity[38, 39]. In the present metabolomics study, we found serum citrulline level was decreased in DZR treatment group and increased in the DOX+ DZR treatment group.…”
Section: Discussionsupporting
confidence: 60%
“…Further, arginine represents a by-product of nitric oxide formation. A previous study showed that nitric oxide levels were decreased in DOX-induced congestive heart failure suggesting the possible role of plasma nitric oxide levels in DOX-induced cardiotoxicity[38, 39]. In the present metabolomics study, we found serum citrulline level was decreased in DZR treatment group and increased in the DOX+ DZR treatment group.…”
Section: Discussionsupporting
confidence: 60%
“…While the basal NO production regulates the cardiomyocyte contractility and the blood flow, the excessively produced NO is involved in cardiac pathologies such as dilated cardiomyopathy and congestive cardiac failure [9,17,18,19]. Recent trials reported that NO was involved in the cardiotoxicity of DOX [10,11,13,20,21]. …”
Section: Discussionmentioning
confidence: 99%
“…The literature data included reduced activity, weight loss, and acid formation as the clinical findings for DOX-associated toxicity. Guerra et al reported that those with cardiomyopathy findings among rats that were administered a cumulative DOX dose of 13.5 mg/kg had significantly lower weight gain relative to the control group [11]. In the trial by Hirano et al, the rats receiving intravenous DOX weekly at a dose of 1.25 mg/kg (total dose: 5 mg/kg) and 2.5 mg/kg for 4 weeks (total dose: 10 mg/kg) exhibited reduction in weight in line with the cardiomyopathy findings; this was particularly marked in the group receiving the dose of 2.5 mg/kg/week [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations